Analysis of ignition and flame geometric characteristics of lubricating oil leaking from automotive engine onto hot surfaces - Bai, Lei; Liu, Changchun; Wang, Liubing (PloS one, 2025)
The ignition and combustion process of lubricating oil leaking from an automotive engine onto a hot surface is a major cause of vehicle fires, and the geometric characteristics of the flame directly affect the spread and severity of the fire. Therefore, studying the ignition characteristics of lubricating oil on hot surfaces and quantifying flame behavior is of great significance for vehicle fire safety protection. This study utilizes a self-developed automotive hot surface ignition oil simulation platform, employing the SOBEL threshold segmentation algorithm combined with box-counting fractal dimension theory. It investigates the factors affecting the ignition delay time of automotive engine lubricating oil, the ignition risk and probability on engine hot surfaces, and analyzes the temporal evolution characteristics of the flame fractal dimension of engine lubricating oil. This research provides theoretical support for vehicle fire risk assessment and prevention. The main findings of this study are as follows: (1) As the temperature of the hot surface increases, the ignition delay time generally shows a decreasing trend, with 450°C being a critical turning point; (2) There is an overlap between ignition and non-ignition cases within a specific range, forming a possible ignition zone, and the R ² values of the fitting equations for the upper and lower boundaries are both above 95%, indicating a good fit. (3) The fractal dimension can effectively quantify the geometric complexity of the flame’s outer contour, thereby characterizing the stability of the flame’s combustion. The evolution of the fractal dimension of the lubricating oil droplet flame shows a trend of first increasing and then slowly decreasing. The interval from 0 to 1 second is the stable combustion phase, from 2 to 3 seconds is the unstable combustion phase, and from 3 to 5 seconds is the secondary stable combustion phase. During this period, the fractal dimension gradually decreases from the peak to around 1, and the flame’s outer contour transforms from complex to simple. (4) The volume of the droplet ( V ) affects both the peak value of the fractal dimension ( D max ) of the flame and the time at which it occurs ( t max ). The larger the volume, the earlier D max occurs. For a 0.1 ml droplet, D max occurs earliest ( t max = 1.98 s), while for a 0.5 ml droplet, D max appears the latest ( t max = 3.22 s). There is a significant correlation between t max and droplet volume V ( R = 0.995, P = 0.001). The spray hole size has a greater impact on D max compared to t max . With spray hole diameters ranging from 0.4 mm to 0.7 mm, the fractal dimensions of all droplet flames appear at around 2.6 seconds, but the values of D max vary significantly. As the spray hole diameter ( S ) decreases, D max approaches 2. When the spray hole diameter is 0.4 mm, D max is the highest, reaching 1.605, indicating the most drastic change in the geometric complexity of the flame’s outer contour and the least stable combustion process overall.